Konsep Tasfiah dalam Islam: Sejarah Dahulu dan Kini - Idris Sulaiman; Aminudin Basir; Mohamad Sabri Haron; Fadlan Mohd Othman (USIM Press, 2024)
Vol. 17 No. 1 (2021): Journal of Maʿālim al-Qurʾān wa al-Sunnah